The three-dimensional culture of L929 and C2C12 cells based on SPI-SA interpenetrating network hydrogel scaffold with excellent mechanical properties - Ma, Chunmin; Gao, Xinru; Yang, Yang; Bian, Xin; Wang, Bing; Liu, Xiaofei; Wang, Yan; Su, Dan; Zhang, Guang; Qu, Lizhe; Zhang, Na (Frontiers in Bioengineering and Biotechnology, 2024)
Cell-cultured meat, which is obtained by adsorbing cells on the three-dimensional scaffold, is considered a potential solution to animal welfare issues. Edible and safe cell-cultured meat scaffolds are a key part of its research. Soy protein isolate (SPI) hydrogel has a three-dimensional network structure and has been studied for L929 cell culture because of its non-toxicity and biocompatibility. However, the toughness and mechanical properties of SPI hydrogel are not enough to bear the requirements of cell cultivation. In this paper, sodium alginate (SA) was added to SPI hydrogel, and the interpenetrating polymer network (IPN) technology was used to construct SPI-SA IPN hydrogel by transglutaminase and Ca 2+ double crosslinking method. SPI-SA IPN hydrogel has excellent mechanical properties, structural stability and biodegradable performance than SPI hydrogel. The bio-compatibility and degradability of L929 and C2C12 cells on SPI-SA IPN hydrogel were studied by cytotoxicity, trypan blue and living/dead cell staining, and the growth law of the hydrogel as a scaffold for cell culture was analyzed. The results showed that L929/C2C12 cells can proliferate normally and adhere in hydrogel and have good bio-compatibility. L929 cells with size about 20-50 µm have better adhesion and growth abilities on SPI-SA IPN hydrogel than C2C12 cells with 100-300 µm. Therefore, the SPI-SA IPN hydrogel is non-toxic and supports the growth of cells in the pores of the material.This study provides a reference for the application of SPI-SA IPN hydrogels in vitro cell growth.